The effect of Isabel grape addition on the physicochemical, microbiological and sensory characteristics of probiotic goat milk yogurt. Issue 6 (28th April 2017) - Silva, Francyeli Araújo; de Oliveira, Maria Elieidy Gomes; de Figueirêdo, Rossana Maria Feitosa; Sampaio, Karoliny Brito; de Souza, Evandro Leite; de Oliveira, Carlos Eduardo Vasconcelos; Pintado, Maria Manuela Estevez; Ramos do Egypto Queiroga, Rita de Cássia
Abstract : The influence of Isabel grape addition on the quality characteristics of probiotic goat milk yogurt were evaluated during refrigerated storage. Abstract : Goat milk is an attractive food because of its nutritional properties, easy digestibility and hypoallergenicity. Goat milk yogurt is an appropriate matrix for the inclusion of new ingredients such as probiotic cultures, fruit and its derivatives. Grapes are rich in polyphenols and recognized for their health benefits. The aim of this study was to improve the quality characteristics of probiotic goat milk yogurt by the addition of an Isabel grape ( Vitis labrusca L.) preparation (IGP). For this, the influence of the addition of IGP on the physicochemical, microbiological and sensory characteristics of goat milk yogurt containing the probiotic Lactobacillus acidophilus LA-05 was evaluated during 28 days of refrigerated storage (5 ± 0.5 °C). Four yogurt formulations were prepared, each varying in the added IGP amount, as follows: Y0 (not containing IGP), YG15 (containing 15 g per 100 mL of IGP), YG20 (containing 20 g per 100 mL of IGP), and YG25 (containing 25 g per 100 mL of IGP). All formulations showed probiotic counts ranging from 7 to 8 log CFU mL −1 over the assessed storage period. The addition of 20 g per 100 mL of IGP affected positively the colour, viscosity, and sensory acceptance of the yogurt formulations. The production of goat milk yogurt containing L. acidophilus LA-05 and IGP is an option for developing a new goat dairy product with added value due to the inclusion of components with potential functional properties.